The Labor of Informational Democracy: A Library and Information Science Framework for Evaluating the Democratic Potential in Socially- Generated Information - Cope, Jonathan (Progressive community action: Critical theory and social justice in library and information science, 2016)
This essay outlines a framework that LIS can use to analyze socially-generated information. The proposed evaluative framework involves three democratic horizons of analysis: the level of access, the level of production, and the level of communicative speech. This inquiry synthesizes the political economy of communication/librarianship, autonomist Marxist insights about the dematerialization of labor in late capitalism, and the concerns of contemporary democratic theory. The essay concludes with a set of proposals for LIS to pursue research and policies that use a critical theoretical framework linking the realm of production (i.e., labor) with communicative democracy.
Keywords: MARX, Karl, 1818-1883; dematerialization of labor; informational democracy; late capitalism

Addressing the Negative Consequences of the Information Age Lessons from Karl Polanyi and the industrial revolution: A note on the politics of theorizing technology - Rogerson, Kenneth (Information, Communication & Society, 2003)
One of the great dilemmas of the information age is the tension between two dynamics: (1) the tendency of information to be free-flowing and not to lose its value as it moves and (2) the tendency to want to control that flow of information in order to profit from its value. In 1944, Karl Polanyi identified similar contradictions in the industrial revolution, except the flowing material was capital instead of information. He spent a lifetime exposing what he felt to be the negative consequences of this increasingly free-flowing capital, the hallmark of a free market economy. He advocated for a welfare state in which government intervention is necessary to control these negative effects. Given issues of the information age such as the digital divide, the commoditization of information, and security and privacy, as well as the arguments of the proponents and critics of these issues, Polanyi's concepts can provide insight into the complexities of increasingly technical and information-based societies.
Keywords: industrial revolution; information technology

Chapter 7: Karl Polanyi - Rogerson, Kenneth S.; May, Christopher (Key Thinkers for the Information Society, 2002)
This article presents Karl Polanyi's analysis of the dynamic relationships between economy and society in the information age. Of the many concepts Karl Polanyi provides in his analysis of economic relations, three stand as carefully calculated assumptions about the relationship between society and economy: the embeddedness of information in society, the commoditization of information and the existence of a double movement in the information revolution. Information has always been embedded in societal interactions. To emphasize this point, he said that the simple flow of information seems to have little effect in and of itself on the outcome of social interchanges. In Polanyi's words, it is also embedded in other social relations, such as political, economic, cultural, or health-related discussions and actions. On the issue of information commoditization, Polanyi takes a different view. His logic indicates that there will be negative social consequences associated with it. One example is digital divide or the discrepancies on a global or national level between those who have access to information through new technologies and those who do not. With regards to the existence of double movement, Polanyi believed that there are two opposing forces-economic liberalism and social protection-present during the industrial revolution. However, this is not easy to see in the information age because of simple paradox. First, people who would eschew the uses of technology for ideological reasons,may turn to it for other reasons. And second, there is only a protest of a specific issue and not the imbalance of information flows or the ownership of information dissemination methods.
Keywords: commercialization; communication revolution; digital divide; industrial revolution; information technology; liberalism